Acceptability of Novel Life Logging Technology to Determine Context of Sedentary Behavior in Older Adults - Harvey, Juliet A (AIMS Public Health, 2016)
OBJECTIVE: Lifelogging, using body worn sensors (activity monitors and time lapse photography) has the potential to shed light on the context of sedentary behaviour. The objectives of this study were to examine the acceptability, to older adults, of using lifelogging technology and indicate its usefulness for understanding behaviour. METHOD: 6 older adults (4 males, mean age: 68yrs) wore the equipment (ActivPAL™ and Vicon Revue™/SenseCam™) for 7 consecutive days during free-living activity. The older adults' perception of the lifelogging technology was assessed through semi-structured interviews, including a brief questionnaire (Likert scale), and reference to the researcher's diary. RESULTS: Older adults in this study found the equipment acceptable to wear and it did not interfere with privacy, safety or create reactivity, but they reported problems with the actual technical functioning of the camera. CONCLUSION: This combination of sensors has good potential to provide lifelogging information on the context of sedentary behaviour.